Peer groups and children's development - Howe, Christine (Chichester, U.K. ; Malden, MA. : Wiley-Blackwell, 2010)
Peer Groups and Children's Development considers the experiences of school-aged children with their peer groups and its implications for their social, personal and intellectual development: Focuses on the peer group experiences of children attending school in Western societies, from five years of age through to adolescence; Considers peer groups in classrooms, friendships made within and outside of school, and the groups that children participate in for extra-curricular activities; Includes a final summary which brings together the significant implications for theory, policy and practice; Uniq.
Peer groups in a cultural context -- Peer groups and classroom structure -- Performance and cooperation in classrooms -- Cooperative interaction and curriculum mastery -- Friendship, status, and centrality -- Individual differences in informal experiences -- Social and personal adjustment -- School performance revisited -- Implications for practice and future research.
Includes bibliographical references and index.
Print version record.
Keywords: Child development; Interpersonal relations in children; Friendship in children; Age groups; FAMILY & RELATIONSHIPS -- Child Development; Age groups; Child development; Friendship in children; Interpersonal relations in children; Electronic books